The Acceptability and Nurtrient Content of Kue Ku With The Utilization of Centella Leaf Essence (Centella asiatica L. Urban) as Natural Content for Healthy Snacks During The SARS COVID-19 Pandemic - Hakim, Lukman (Jurnal Gizi dan Kesehatan Nusantara, 2022)
The SARS COVID-19 pandemic is an infectious disease that has spread in various parts of the world caused by SARS-CoV-2. As an effort to minimize inflammatory effects by optimizing the immune system in the body, adequate intake is needed. Kue ku with the use of centella asiatica leaf essence can be a healthy snack rich in macronutrients and micronutrients. This study aims to analyze the addition of centella asiatica leaf essence as a natural dye to the acceptability and nutritional value. The research method is pure experimental using a Complete Randomized Design (CRD) design with 3 treatments in the form of adding centella asiatica leaf essence to kue ku with a percentage of 15%, 30% and 45%. The panelists in this study were 5 trained panelists as well as 30 semi-trained panelists. The data collection technique in this study used a sensory test based on the level of favorability, then the analysis technique used descriptive analysis and statistical analysis of the Kruskal-Wallis non-parametric test with the Mann Whitney advanced test at a 95% confidence level (p<0.05). The results showed that there was an influence of formulation on color characteristics (p=0.017). For aroma, texture, taste and overall parameters indicate the insignificant differences (p>0.05). The most preferred sample treatment was the P3 kue ku sample (addition of 45% centella asiatica leaf extract). The nutritional content of the best product of the P3 kue ku sample in the form of energy, protein, fat, carbohydrates, vitamin C and iron is 185 g, 5.7 g, 5.2 g, 28.7 g, 14.6 mg and 5.3 mg